Big Data Analysis and Deep Learning Applications Proceedings of the First International Conference on Big Data Analysis and Deep Learning - Zin, Thi Thi; Lin, Jerry Chun-Wei (Advances in Intelligent Systems and Computing,, 2019)
This book presents a compilation of selected papers from the first International Conference on Big Data Analysis and Deep Learning Applications (ICBDL 2018), and focuses on novel techniques in the fields of big data analysis, machine learning, system monitoring, image processing, conventional neural networks, communication, industrial information, and their applications. Readers will find insights to help them realize more efficient algorithms and systems used in real-life applications and contexts, making the book an essential reference guide for academic researchers, professionals, software engineers in the industry, and regulators of aviation authorities. .